Analisis Waktu pengerukan Check Dam Timur Terhadap Laju Erosi di Das Timur Tambang Batu Kapur PT Semen Padang - Tomi Suprianto Simatupang; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2022)
PT. Semen Padang is a state-owned enterprise (BUMN) engaged in limestone and silica mininglocated in Bukit Karang Putih, Indarung, Lubuk Kilangan District, Padang City, West Sumatra. The miningsystem applied by PT. Semen Padang is an open pit mining system (surface mining) with an open pitmining method. Activities include pioneering, cleaning of drilling areas (dozing), drilling (drilling), blasting(blasting), loading (loading), and material transportation (hauling) from the loading area to the crusher.Rainfall data used are rainfall intensity 192,309 mm/hour, total discharge of 57.488 ????3 /s, suspendedresidue 977,296 g/s, incoming solids volume of 0.48865 x 10−3????3 /s, the percentage of solids entering :solid is 0.000005 % and the percentage of water is 99.99995 %, and the sedimentation volume is15.410.066 ????3 /thn. The dredging interval is once every 125 days, and the remaining life of the check damuntil the intake is closed is 1.3682 years. Based on the results of research and observations during theresearch process, the authors would like to give suggestions, namely:. so that check dam maintenancecan be carried out continuously, especially in preventing the accumulation of sediment so that there is noexcessive amount of water, especially during the rainy season which can result in equipment damage andunsafe working conditions.Keywords: East Chekdam, Volume, Maintenance, Rainfall.